2002
DOI: 10.1530/eje.0.1460767
|View full text |Cite
|
Sign up to set email alerts
|

Objective estimates of the probability of developing hypothyroidism following radioactive iodine treatment of thyrotoxicosis

Abstract: Objective: Several risk factors have been shown individually to influence the outcome following radioactive iodine (RAI) therapy in the treatment of hyperthyroidism. However, no attempt has been made to determine their independent prognostic values that could be used in a regression model to provide objective estimates of the probability of developing hypothyroidism. Study design and methods: We audited records of all hyperthyroid patients treated with first dose RAI between 1980 and 1996. Patients were aetiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 29 publications
2
39
2
2
Order By: Relevance
“…There are only few previously published long-term follow-up studies regarding radioiodine treatment of hyperthyroidism in patients (15,21,22). It was observed that hypothyroidism will develop in 82% of patients with Graves' disease and in 32% of patients with multinodular goiter treated with 131 I within 25 years (15).…”
Section: Discussionmentioning
confidence: 99%
“…There are only few previously published long-term follow-up studies regarding radioiodine treatment of hyperthyroidism in patients (15,21,22). It was observed that hypothyroidism will develop in 82% of patients with Graves' disease and in 32% of patients with multinodular goiter treated with 131 I within 25 years (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other recent studies (12,29,30) performed in order to evaluate the efficacy of 131 I therapy, we included patients with both autoimmune (Graves' disease) and non-autoimmune hyperthyroid diseases. Our finding of no radioprotection of methimazole, among patients with either Graves' disease or toxic nodular goitre, is in contrast to the findings by Körber et al (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that the presence of thyroid autoantibodies in patients with GD prior to 131 I therapy is an independent predictor of the occurrence of hypothyroidism (9). Furthermore, high titers of TRAb in patients with GD prior to 131 I therapy are associated with treatment failure, whereas elevated TRAb following 131 I therapy predicts the occurrence of hypothyroidism (10).…”
Section: Introductionmentioning
confidence: 99%